Social Media and Motivations: Stories of English Education Students in EFL Learning - Khoirunnisa, Firda Natasya; Anjaniputra, Agung Ginanjar (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2024)
People need motivation to act, to learn, and to do something. English must now be part of globalization, and so does the technology. Social media, as one of the results of technology, has been used by people worldwide. The massive use of social media in this era helps students to learn English. This study seeks out what motivates students in teacher education programs to continue to learn English in college and what their motivations are to learn through social media. This study collected answers from five participants of English Education students with a narrative inquiry method through students' journals and interviews. The data showed that students enrolled in the English Education program for many reasons, including their interest in English since high school, their parents, and even their environment. After being accepted into an English Education program, students relied on the lecturers' materials and learn English through social media. English Education students were motivated to learn English through social media mostly because social media provided many interesting contents which were fun and have flexibility to access. The social media used by students were mostly YouTube, followed by X, Facebook, Discord, TikTok, and Instagram. In conclusion, students enroll in English education programs for many reasons. However, all students tried to learn English through other media, such as social media, since it provided many beneficial contents.